Small Voices, Big City: Reconfiguring Urban Governance through Child Participation in Surabaya - Hastira, Muhammad Fajhriyadi (Global Focus, 2026)
This study aims to analyze the implementation of the Child-Friendly Cities Initiative (CFCI) in Surabaya and the dynamics of children's participation in urban development. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis, involving policy makers, the Children's Forum, and local communities. Thematic analysis reveals the adaptation of global CFCI norms to the local context, increased meaningful participation of children, and challenges such as resource constraints and inter-sectoral coordination. The findings enrich the literature on norm localization and meaningful involvement, with implications for strengthening policies, replicable models in other cities, and the development of sustainable child participation.